Carte Postale de Paris Avec Tabouret Tour Eiffel 1973 - Ditigibt (NC, 2026)
Postcard of Paris. Motive: "Eiffel Tower stool" on the bouquinistes banks of the Seine in Paris, 1973
Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons